Pengaruh Metode Pembelajaran Tebak Kata dan Eksperimen terhadap Minat dan Hasil Belajar Biologi - Tunas Fatimatuz Zahro, Putri; Nurjanah, Umi (FKIP Universitas Islam Jember, 2023)
Learning is the main activity of the educational process. Researches conducted observations in class XI SMA 02 Diponegoro Wuluhan Jember. This study aims to determine the effect of teaching methods charades and experiments of interest and student learning outcomes in study subjects circulatory system Heart. Based on the results of research and learning methods charades experiment did not affect the student’s interest in learning biology XI SMA 02 Diponegoro Wuluhan Jember academic year 2013-2014 for the hypothesis test the significance value of 0.223 is greater than 0.05. the learning methods of charades and experimentation influence the biology student learning outcomes XI SMA 02 Diponegoro Wuluhan Jember academic year 2013-2014 for the hypothesis test significance value of 0.04 less than 0.05